Unemployment insurance benefits and corporate financing decisions : evidence from Europe - Cardoso, Patrícia Amoroso Pinto (2019)
This dissertation aims at presenting new empirical evidence regarding the relationship between unemployment risk and the corporate financing decisions of a firm. More precisely, the intent of the study is to understand how a variation in the costs of unemployment to the employees – using as a proxy the maximum unemployment insurance (UI) benefits a country provides - affects the levels of debt in a firm, as well as its operating performance. The findings indicate that there is no significant relationship between the UI benefits in one year and the changes in the capital structure of a firm the next year. Regarding the second question, empirical results suggest that there is a negative relationship between the two variables, i.e., an increase in the UI benefits will be associated with a decrease in the profitability of a firm the subsequent year.